Penanganan Fisioterapi Kasus Flat Foot Dengan Intervensi Stimulasi - Rehalat, Syani Mustika; Amani, Ghibtah Iradah; Setiawati, Khaerunisa Indah; Alpiah, Dini Nur (JURNAL ILMIAH NUSANTARA, 2025)
. Flexible flatfoot is a common musculoskeletal condition in children, characterized by a decrease in the medial longitudinal arch. Although it is often physiological at a young age, persistence after the age of 6–8 years, especially when accompanied by pain or functional disturbances, requires intervention. Physiotherapy plays a crucial role in conservative management, with stimulation interventions aimed at muscle strengthening and improvement of neuromuscular control emerging as promising modalities. This study aims to describe the physiotherapy management with stimulation intervention in cases of pediatric flexible flatfoot and to analyze its impact on foot posture and function.. Methods: This study used a descriptive qualitative case study design involving three pediatric subjects (D, E, and F), aged 6–8 years, diagnosed with bilateral flexible flatfoot. Each subject received stimulation interventions, including short foot exercises, intrinsic muscle strengthening exercises, balance, and proprioception training, three times per week for eight weeks. The observed and measured parameters included the Foot Posture Index (FPI), Navicular Drop Test, as well as gait and balance observation. Measurements were taken before the intervention (Week 0) and after the intervention (Week 8). The data were analyzed descriptively for each case. Results: All three subjects showed improvement in the measured parameters. Subject D showed a decrease in FPI from +8 to +4 (right) and from +9 to +5 (left), and a decrease in Navicular Drop from 12 mm to 8 mm (right) and from 13 mm to 9 mm (left). Subject E showed a decrease in FPI from +7 to +3 (bilateral) and a decrease in Navicular Drop from 11 mm to 7 mm (bilateral). Subject F showed a decrease in FPI from +6 to +2 (bilateral) and a decrease in Navicular Drop from 10 mm to 6 mm (bilateral). Functionally, the observation showed improvements in gait stability and balance ability in all subjects, along with a reduction in complaints such as fatigue or heel pain. Conclusion: Physiotherapy management with stimulation intervention demonstrated effectiveness in improving foot posture and function in children with flexible flatfoot. This intervention helps strengthen the arch-supporting muscles and improve neuromuscular control, contributing to arch correction, stabilization, and better movement quality in children.